Hydraulic permeability prediction from attenuation in an oil well using the squirt flow model - Joseline Mena-Negrete; Raúl Del Valle García; Enrique Coconi-Morales (Geofísica Internacional)
A practical methodology is presented for estimating the hydraulic permeability from the wave attenuation at sonic frequencies using the poroelastic squirt flow model associated with the mechanism that encompasses the interaction between solid and fluid in an oil well. The methodology consists of four stages: a) the petrophysical evaluation, b) the static rock physics modeling that includes its diagnostics, c) the estimation of wave attenuations using an inversion scheme to optimize the Z critical parameter from the squirt flow model, d) the correlation between attenuations and the Z parameter with hydraulic permeabilities obtained by conventional well logs and available core analysis. The correlations are the means to establish the predicted hydraulic permeabilities from sonic and ultrasonic data. The obtained results suggest that the Z parameter is low while attenuations are high when the medium presents high porosity and permeability. In the methodology, the inversion scheme is proposed to find the Z parameter, the velocity dispersion, and attenuations in terms of the inverse quality factors, respectively for P-wave (QP –1) and S-wave S (QS –1) using a simulated annealing technique. The results from the application of the methodology are validated with core data (water saturation, porosity, and permeability) and mineralogical analysis from thin sections by the point counting technique. This methodology promises a means for predicting the hydraulic permeability from sonic and ultrasonic velocities in a well.